The Gambia has eliminated trachoma as a public health problem: Challenges and successes. - Agatha Aboe; Balla Musa Joof; Sarjo Kebba Kanyi; Abba Hydara; Philip Downs; Simon Bush; Paul Courtright (PLoS Neglected Tropical Diseases, 2022)
Trachoma is the leading infectious cause of blindness in the world and has been known to be a major public health problem in The Gambia for over 60 years. Nationwide blindness surveys, including trachoma, in 1986 and 1996 provided the foundation for a comprehensive plan to implement a trachoma elimination strategy. Impact and pre-validation surveillance surveys in 2011-13 demonstrated that active trachoma was below WHO threshold for elimination but trichiasis remained a public health problem. Trichiasis-only surveys in 2019 demonstrated that trichiasis was below WHO thresholds for elimination and in 2020 the Government of The Gambia completed and submitted its dossier for validation of elimination as a public health problem. Challenges that The Gambia faced on the pathway to elimination included effective use of data for decision making, poor trichiasis surgical outcomes, lack of access to antibiotic treatment for low prevalence districts, high attrition of ophthalmic nurses trained as trichiasis surgeons, unexpected active trachoma in madrassas, the misalignment of elimination of active trachoma and trichiasis, trichiasis in urban settings, and maintaining the quality of surgery post-elimination when trichiasis cases are rare. Elimination of trachoma does not end with the submission of an elimination dossier; The Gambia will need to sustain monitoring and support over the coming years.